Response of the Five Highbush Blueberry Cultivars to In Vitro Induced Drought Stress by Polyethylene Glycol - Sabin Molnar; Doina Clapa; Viorel Mitre (Agronomy, 2022)
Stress caused by drought is an important factor that affects the growth and development of highbush blueberry plants. In vitro screening for drought stress tolerance is of major importance in identifying cultivars that have optimal stress tolerance and productivity. The aim of this study was to evaluate the responses of five in vitro-grown highbush blueberry cultivars (Bluecrop, Brigitta Blue, Duke, Goldtraube and Hortblue Petite) under drought stress. Five concentrations of polyethylene glycol (PEG 6000), 0 g/L, 10 g/L, 20 g/L, 30 g/L, 40 g/L, 50 g/L, were applied to induce drought stress in the culture media. Significant differences were found in shoot length and number, proliferation rate, fresh weight, dry weight, water content, chlorophyll, and carotenoid content. Drought stress had a negative impact on shoots length, chlorophyll, and carotenoid content for all highbush blueberry varieties. The conclusion of the study highlights that Goldtraube had the highest drought tolerance efficiency, followed by Bluecrop, Hortblue Petite, Duke, and Brigitta Blue.